Trunk rotation enhances movement of the knee abduction angle while running among female collegiate middle- and long-distance runners - Kurihara, Y.; Ohsugi, H.; Karasuno, H.; Tagami, M.; Matsuda, T.; Fujikawa, D. (Journal of Human Sport & Exercise, 2022)
This cohort study aimed to i) clarify the relationship between abduction of the knee joint and trunk motion during running in the stance phase, and ii) clarify the relationship between abduction of the knee joint during running in the stance phase and the amount of trunk rotation measured in a static position. Twenty-nine female collegiate middle- and long-distance runners participated. The knee abduction angle and absolute angles to the floor were calculated using a three-dimensional motion analysis device. Static trunk rotation was calculated. Trunk rotation angle to the supporting side (r = 0.525), thigh posterior tilt angle (r = -0.510), thigh adduction angle (r = 0.417), lower leg anterior tilt angle (r = -0.483), and static trunk rotation to the supporting side (r = -0.429) were significantly correlated with knee abduction angle. Trunk rotation angle to the supporting side (ß = 0. 465), thigh adduction angle (ß = 0.374), lower leg anterior tilt angle (ß = 0.228), and static trunk rotation to the supporting side (ß = -0.256) (R2 = .556) were significantly correlated with the knee abduction angle. The increase or decrease in the knee abduction angle should consider the mutual influence of the lower limb and trunk motion.